O Centro Ecumênico de Cultura Negra (CECUNE) e suas ações educativas - Lira, Lilian Conceição da Silva Pessoa de (2006)
This present work is a result of qualitative research in the religion and education area, its focus is in an experience constructed by a social segment which answers to the necessity of an intervention as a historical subject in the context of the social relations demarcated by the racial relations in Brazil. This work presents the Centro Ecumênico de Cultura Negra (CECUNE), a non-governmental organization in the city of Porto Alegre, which has acted in the State of Rio Grande do Sul for twenty years. This dissertation seeks to point out its action in the Black Movement and the Ecumenical Movement, and its educative actions as effective contributions in the continuous and necessary process of transformation of the society. As well, this work analyzes some results of its partnership with the Centro Universitário Metodista IPA as an example of educative action for inclusion of black poor women and men in the university, proposing perspectives which will give continuity of this research at the doctoral level in the future.